SOCIALIZATION OF ENTREPRENEURSHIP THE REGARDING OF SELLING PRICES IN THE OFFERING MSME PRODUCT TO VOCATIONAL HIGH SCHOOL STUDENTS - Hermawansyah, Adi; Cipto, Rahajeng Cahyaning Putri; Artikasari, Devi; Triana, Alvina Alda; Sasih Kirani, Amanda Retno; Bunga, Ardiyanto Fernando; Darmawan, Darmawan; Zuhra, Faza Muraya; Ferdinand, Gregorius Ergi; Ardiana, Ira Maya; Sari, Junita Dewi Indah; Akmal, Muhammad Firja (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Micro, Small and Medium Enterprises (MSME) is an important part of the economy of a country or region, especially in Indonesia. The development of micro, small and medium enterprises has an important meaning in encouraging national economic growth and reducing is poverty. The development of MSME sector is often described as one of the factor for successful development, especially for those with low per capita income. One of the key factors in the success of MSME is their ability to determine the right product selling price. The right selling price can help MSME achieve several goals, such as: Increasing sales, achieving profit targets, competing in the market, attracting consumers and increasin profitability. Determining the selling price of MSME products is a complex process and requires careful consideration and marketing strategies to maximize prices and promotion for the product sales.